Wronskian Addition Formula and Darboux-Pöschl-Teller Potentials - Pierre Gaillard; Vladimir Matveev (Journal of Mathematics)
For the famous Darboux-Pöschl-Teller equation, we present new wronskian representation both for the potential and the related eigenfunctions. The simplest application of this new formula is the explicit description of dynamics of the DPT potentials and the action of the KdV hierarchy. The key point of the proof is some evaluation formulas for special wronskian determinant.